Retrospective evaluation of the applications within the scope of probation implementation: the data of 2018 - Eğilmez, Oğuzhan Bekir; Örüm, Mehmet Hamdi; Dumlupınar, Ebru; Egeli, Aslı (Journal of Dependence, 2019)
Objective: The aim of this study was to investigate the substance use characteristics of people who applied to a general hospital in Turkey within the scope of probationary implementation (PI) in 2018. Method: The study included 368 patients who admitted to Adiyaman Training and Research Hospital within the scope of PI in 2018. Psychiatric interviews were conducted with these individuals and probable psychoactive substances in urine were evaluated with programs consisting of three and/or six applications. Results: 276 patients (75%) completed the program consisting of three applications and 92 patients (25%) completed the program consisting of six applications. There was no significant difference in terms of gender distribution in both programs. There was a significant difference in males in terms of participation in programs of three-time and six-time (47.10%) at the age of 25 and under. Conclusion: PI is a fairly new practice in Turkey, the substance has an important place in the care of addicts. In terms of gender distribution, the results in the literature are consistent with the literature. Alcohol comorbidity of the subjects under control is noteworthy.